Transformation of Higher Education in Russia from the Position of World-System Analysis: Current Trends - Alexander G. Bermous (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The article analyses the individual problems of transformation in higher education in Russia in the first quarter of the 21st century from the standpoint of a sociological approach. It assesses the trends in the modernization of the system of higher education in the period preceding Russia’s withdrawal from the Bologna process. It also evaluates the potential for reforming higher education in the post-Bologna perspective (2022–2026).